Bacillus subtilis PS-216 Spores Supplemented in Broiler Chicken Drinking Water Reduce Campylobacter jejuni Colonization and Increases Weight Gain - Šimunović, Katarina; Sahin, Orhan; Erega, Andi; Štefanič, Polonca; Zhang, Qijing; Mandic Mulec, Ines; Smole Možina, Sonja; Klančnik, Anja (Frontiers in Microbiology, 2022)
Campylobacter jejuni is the leading cause of bacterial gastroenteritis, or campylobacteriosis, in humans worldwide, and poultry serves as a major source of infection. To reduce the risk associated with C. jejuni transmission via poultry meat, effective interventions during poultry production are needed, and the use of probiotics is a promising approach. In this study, 15 Bacillus subtilis strains were initially screened for their anti-Campylobacter activities. B. subtilis PS-216 strain demonstrated the best anti-Campylobacter activity against 15 C. jejuni isolates when examined using in-vitro co-cultures. To evaluate the suitability of B. subtilis PS-216 for probiotic use, its susceptibility to eight clinically important antimicrobials and simulated gastric conditions was investigated. B. subtilis PS-216 was sensitive to all of the tested antibiotics. Although vegetative cells were sensitive to gastric conditions, B. subtilis PS-216 spores were highly resistant. We further evaluated the use of a B. subtilis PS-216 spore preparation (2.5 ×106 CFU/mL water) to prevent and/or reduce C. jejuni colonization in broiler chickens in vivo. Compared to the untreated group, significantly lower Campylobacter counts were detected in caeca of broilers continuously treated with B. subtilis PS-216 spores in their drinking water. Furthermore, broilers continuously treated with B. subtilis PS-216 spores showed improved weight gain, compared to the control group. Together, these results demonstrate the potential of B. subtilis PS-216 for use in poultry to reduce C. jejuni colonization and improve weight gain.